2008
DOI: 10.1007/s00213-008-1260-2
|View full text |Cite
|
Sign up to set email alerts
|

Delta-9-tetrahydrocannabinol (THC) serum concentrations and pharmacological effects in males after smoking a combination of tobacco and cannabis containing up to 69 mg THC

Abstract: This study demonstrates that the known linear association between THC dose and THC serum concentration also applies for high THC doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 20 publications
6
42
2
1
Order By: Relevance
“…The cannabis data used in the analyses were obtained from a double-blind, placebo-controlled, four-way cross-over randomised trial (Hunault et al 2008). The Human Ethics Committee of the medical centre approved the trial, and written informed consent was obtained from all participants prior to their inclusion.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cannabis data used in the analyses were obtained from a double-blind, placebo-controlled, four-way cross-over randomised trial (Hunault et al 2008). The Human Ethics Committee of the medical centre approved the trial, and written informed consent was obtained from all participants prior to their inclusion.…”
Section: Methodsmentioning
confidence: 99%
“…This article focuses on the cognitive and psychomotor effects of such THC doses. The pharmacokinetics and effects on heart rate and blood pressure after smoking cannabis cigarettes with high THC doses have been reported elsewhere (Hunault et al 2008). We previously showed that smoking cigarettes containing a mix of tobacco and cannabis at THC doses up to 69 mg induced a linear increase in serum THC concentration (Hunault et al 2008).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…In our article selection, the highest concentration used to analyze pharmacodynamical effects was 69 mg of 9-THC (23%) (Hunault et al, 2008(Hunault et al, , 2009. Even though high concentrations used in research may be lower than some of the registered potencies, as samples containing between 30% and 40% of 9-THC were reported by several authors.…”
Section: Cannabis Potencies and Implications For Healthmentioning
confidence: 92%
“…One example is analyzing cannabis extracts mixed with tobacco (Hunault et al, 2008(Hunault et al, , 2009Van der Kooy, Pomahacova, and Verpoorte, 2008;Van der Kooy et al, 2009) or volunteers' own preparations (Morgan et al, 2012;van der Pol et al, 2013).…”
Section: Cannabis Potencies and Implications For Healthmentioning
confidence: 99%